Variation in the wheat AP2 homoeologs, the genes underlying lodicule development - Ning, Shunzong (Japanese Society of Breeding, 2013)
The bread wheat genome harbors three homoeologs of the barley gene HvAP2, which determines the cleistogamous/non-cleistogamous flowering. The three homoeologs, TaAP2-A, TaAP2-B and TaAP2-D, are derived from the A, B and D genomes. The importance of lodicule swelling in assuring non-cleistogamous flowering in a range of wild and domesticated wheat accessions of varying ploidy level was established. Re-sequencing of wheat AP2 homoeologous genes was carried out to identify natural variation at both the nucleotide and polypeptide level. The sequences of wheat AP2 homoeologs are highly conserved even across different ploidy levels and no functional variants at the key miR172 targeting site were detected. These results indicate that engineering of cleistogamous wheat will require the presence of a functional TaAP2 modification at each of the three homoeologs.